Time- and amplitude-based voice source correlates of emotional portrayals - Ni Chasaide, Ailbhe; Gobl, Christer; Yanushevskaya, Irena (Springer, 2007)
A detailed analysis of glottal source parameters is presented for emotional portrayals which included both low and high activation states: neutral, bored, sad, and happy, surprised, angry. Time- and amplitude-based glottal source parameters, F0, RG, RK, RA, OQ, FA, EE, and RD were analysed. The results show statistically significant differentiation of all emotions in terms of all the glottal parameters analysed. Results furthermore suggest that the dynamics of the individual parameters are likely to be important in differentiating among the emotions.
Affective Computing and Intelligent Interaction
Keywords: Voice source parameters; Emotion; Inverse filtering; LF model; Digital Engagement; Digital Humanities